PANGAN FUNGSIONAL DARI TEMPE NON-KEDELAI: INDONESIA - Jayanti, Jienny; Rizkaprilisa, Windy (Science Technology and Management Journal, 2024)
Tempeh is a functional food product which is generally made from soybeans. Until now, the need for soybeans is still largely met by imports. Therefore, it is necessary to study the potential of raw materials from non-soybeans from domestic production to replace soybeans. The aim of this review is to determine the potential of non-soybeans in processing tempeh as a functional food. Various non-soybean varieties such as jack beans, green beans, pigeon peas, lamtoro beans, red beans, peanuts, black soybeans, and saga beans, can be used as an alternative to soybeans as a raw material for making tempeh. The process for making tempeh from non-soybeans is in principle the same as the process for making tempeh from soybeans, the differences are in the length of soaking, boiling/steaming and fermentation. The potential protein content in non-soy tempeh has many benefits due to the presence of bioactive compounds. This non-soybean raw material has the potential to be developed as an alternative raw material to substitute soybeans in making tempeh..